Climate change, water quality, and water diversion are associated with the shifts of aquatic vegetation structure and phenology in five temperate regulating lakes of eastern China - Yan Guo; Shilong Ren; Quanzhou Yu; Xiaohui Bai; Shuping Ji; Jinyue Chen; Yi Zhu; Junfeng Xiong; Lei Fang; Chong Liu; Jie Li; Yating Li; et al. (Water Research, 2026)

Soybean residue incorporation enhances soil CO₂ emissions by increasing nutrient availability and alleviating microbial phosphorus limitation - Xiongde Dong; Yutong Xiao; Mai-He Li; Shijie Han; Yating Deng; Yanyan Yu; Feirong Ren; Junqiang Zheng (Applied Soil Ecology, 2026)

Decoding the partitioning behavior of poly- and perfluoroalkyl substances: Insights from human liver and blood biomonitoring with machine learning - Linping Cao; Yishu Zheng; Wenfei Yu; Jiaqi Shao; Yu Fu; Yating Liu; Weichen Zhang; Jiamian Fang; Yuanchen Chen; Hangbiao Jin (Environmental Pollution, 2026)

Defect engineering oxygen vacancies via synergistic tungsten substitution and water quenching in V2O5 cathodes for high-performance zinc-ion batteries - Jianwei Wang; Lin Xu; Yating Yu; Jianzhao Liu; Qianhui Zhang; Wenlin Zhang; Xinyue Wang; Jihong Bian; Yanzhong Zhen; Daniel Q. Tan (Chemical Engineering Journal, 2026)

Dual character of atmospheric NH3 on NH4NO3 aerosols — reducing evaporation indicated by perturbation analysis versus promoting formation predicted by thermodynamic modeling - Yinghua Lai; Qinchu Fan; Yating Gao; Lei Sun; Yang Gao; Huiwang Gao; Huaming Yu; Xiaohong Yao (Atmospheric Environment, 2026)

Association between gut microbiota composition and liver dysfunction in school-aged children exposed to triclosan - Aijing Li; Menglong Li; Wang Xu; Yanhui Zhang; Shulan Yin; Yating Yu; Shufa Zheng; Yifei Hu; Maoyong Song (Journal of Environmental Sciences, 2026)

Green antimicrobial intervention during pre-cooling: ultrasound-enhanced lactic acid improves chicken meat quality — insights from molecular dynamics and volatile profiling - Tianran Huang; Yating Liu; Lingqi Li; Yujia Yang; Guiming Li; Lei Wang; Yu Huang; Mingye Wu; Guanghui Li; Qingyong Zhang; Huixiao Liu; Peng Wang (Food Research International, 2026)

Long-term exposure to air pollution, proteomic aging clocks, and liver-related outcomes in Chinese adults - Yating Huang; Dong Sun; Axing Lv; Jun Lv; Canqing Yu; Dianjianyi Sun; Pei Pei; Ling Yang; Yiping Chen; Huaidong Du; Dan Huang; Xiaoming Yang; et al. (Environmental Research, 2026)

Mechanism-oriented Object–Environment–Emotion (OEE) framework for urban flood disaster assessment using multimodal social media - Yating Fan; Yuefan Li; Zhihao Shen; Da Kuang; Yu Yan (Sustainable Cities and Society, 2026)

Functional interaction between Bacillus velezensis D103 and maize reveals a microbial mechanism for drought stress mitigation via photosynthesis and sugar metabolism - Yating Zhang; Zhenqiang Feng; Yanling Guo; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Bo Zhang; FangFang Yu; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; et al. (Plant Science, 2026)

Unraveling the size-dependent toxicity mechanisms of polystyrene microplastics on coral symbiotic Symbiodiniaceae: Integrated physiological and transcriptomic perspectives - Jiayuan Liang; Yating Yang; Tianyi Niu; Zhicong Li; Zhuqing Liang; Mingyao Lu; Li Zhang; Yihe Feng; Sanqiang Gong; Kefu Yu (Marine Pollution Bulletin, 2026)

Myeloid PKM2 deficiency alleviates allergic airway inflammation and promotes macrophage efferocytosis via SLC13A3 - Lingli Chen; Yile Liu; Yating Chen; Yue Zhang; Lei Yu; Yantong Zhu; Wang Peng; Maolan Wu; Xiangrong Zheng (Inflammation Research, 2026)

Prediction of freeze–thaw interface depth in a permafrost highway embankment using variational mode decomposition and a CNN–LSTM hybrid model - Yating Jiang; Ding Wang; Yu-zhi Zhang; Meng Wang; Jianbing Chen; Kun Yuan (Transportation Geotechnics, 2026)

The transformation of China's iron and steel industry under carbon constraints: A balance between economy, emission reduction and technical feasibility - Hua Tong; Jun Liu; Yu Wang; Haowen An; Ge Song; Yating Hou; Xiaolong Tang; Honghong Yi (Journal of Environmental Sciences, 2026)

L-xylulose, a new versatile rare sugar: recent biosynthetic advances and challenges - Xiaolan Li; Yating Liang; Guoyan Zhang; Jingqiong Wan; Yifan Yu; Zhongyi Hua; Zhi-Hong Zhang; Xianghui Qi; Zhen Ouyang (Food Research International, 2026)

Integrating filtration, pollutant adsorption, and thermal management for enhanced respiratory health: A synergistic framework for next-generation protective masks - Yating Tang; Yun Su; Yiwei Wu; Zhuoling Yu; Mengxian Xu; Miao Tian; Jun Li (Building and Environment, 2026)

Correction to: Automated machine learning-based reverse osmosis membrane flux prediction and chemical dosage dynamic adjustment - Zhiyang Cheng; Yang Yu; Xia Meng; Yating Wang; Fangong Kong; Minghua Zhou; Jie Wang (ENGINEERING Environment, 2026)

Heteroatom-doped MXene quantum dots: red emission tuning and dual-functional performance - Fanyong Yan; Ruixue Bai; Yating Li; Shanshan Li; Jinyun Xu; Juanru Huang; Yu Wang; Yang Fu (Analytica Chimica Acta, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

Directed charge transfer in a chitosan-citric acid/NH2-UiO-66 hybrid via an amide bond bridge for photocatalytic co-production of benzaldehyde and H2O2 - Yating Lu; Huixia Zhu; Yue Han; Yu Tian; Xiaoxia Liang; Dongyu Nie; Tingming Ye; Yixu Peng; Xia Yang (Chemical Engineering Journal, 2026)

Building 3D conductive networks within sponge-like porous carbon nanofibers: A CNT-based cathode strategy for superior microbial fuel cells - Wei Huang; Yating He; Wenyi Yan; Longfei Qiao; Yu Tao; Xiangyu Wei; Xiumei Song; Lin Yang; Lichao Tan; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2026)

Coordinating food security and ecological pressures in the North China Plain: A Doughnut framework approach - Yating Dai; Le Yu; Bowen Cao (Agricultural Systems, 2026)

Behavior recognition of grazing cattle with hybrid segmentation of multi-sensor features - Yuxiao Yue; Yating Hu; Luyu Ding; Chaoyuan Wang; Qifeng Li; Ligen Yu; Baozhu Yang (Computers and Electronics in Agriculture, 2026)

Integrative metabolomics and machine learning reveal the toxic mechanisms of elaidic acid in polycystic ovary syndrome - Yating Xu; Li Ning; Ruyue Wang; Hua Ma; Hongting Zhao; Yu Si; Xiu Li; Qingling Ren (Reproductive Toxicology, 2026)

UiO-66 porous liquids with synergistic catalytic effects for promoting efficient CO2 conversion - Yaru Lu; Ruyu Bai; Dechao Wang; Yangyang Xin; Weirui Zhang; Fangfang Su; Zheng Dong; Wendi Fan; Yating Zhang; Fangli Yu; Xin Li; Yingying Zhou; et al. (Chemical Engineering Journal, 2026)

The synergistic effect of ambient PM2.5 and psychosocial stress on cardiac health: evidence from a multi-center panel study - Yang Lan; Xianggui Li; Jian Lei; Weidong Zhang; Yunxing Jiang; Kai Wang; Lei Lei; Cuiyao Xie; Yu You; Jiaqi Zhu; Tong Wu; Jie Yan; et al. (Environmental Research, 2026)

Study on the suppression and CO elimination effect of Co3O4 catalyst on coal dust-methane mixed explosion - Xiaoyu Chen; Yating Liu; Jiaxin Shi; Bingjie Wang; Shuo Gao; Junyi Li; Xuan Xu; Jian Li; Yu Zhang; Chuyuan Liu; Jiahao Li; Mingya Wen; et al. (Fuel, 2026)

Melatonin alleviates UV-induced embryonic toxicity via PARP1 expression in early mouse embryos - Yating Zhu; Jing Zhang; Mengyao Wang; Yaxin Chen; Peiwen Wang; Yuan Jiao; Zhixin Pu; Hongzhen Ruan; Biao Yu; Dongmei Ji; Weiwei Zou; Yajing Liu; et al. (Environmental Pollution, 2026)

Color disparity enhances the toxic effects of polystyrene microplastics on Cladocopium goreaui - Tianyi Niu; Yating Yang; Sanqiang Gong; Kefu Yu; Jiayuan Liang (Marine Pollution Bulletin, 2026)

Using machine learning to deeply analyze the critical role of trace element additives in anaerobic digestion and guide the optimization of addition strategies - Yating Yu; Yi Zhang; Yijing Feng; Zheng Hao Leong; Junting Pan; Jianping Su; Yeqing Li (Water Research, 2026)

Optimization of extraction methods, component identification of bound polyphenols from sea-buckthorn pomace, and its ameliorative effects on oxidative stress in sleep-deprived mice - Jing Peng; Xin Li; Mingyou Yuan; Yating Tang; Tianyi Qiao; Jiaying Li; Haoyang Yu; Meng Zhang; Xiulian Li; Ying Lan (Food Chemistry, 2026)

Bacillus velezensis D103 enhances maize drought tolerance via ROS-scavenging and phenylpropanoid pathway activation - Yating Zhang; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Fangfang Yu; Bo Zhang; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; Ning Zhang; Bingxue Li (Plant Cell Reports, 2026)

Automated machine learning-based reverse osmosis membrane flux prediction and chemical dosage dynamic adjustment - Zhiyang Cheng; Yang Yu; Xia Meng; Yating Wang; Fangong Kong; Minghua Zhou; Jie Wang (ENGINEERING Environment, 2026)

Comparative Population Genomics of Relictual Caribbean Island Gossypium hirsutum - Weixuan Ning; Guanjing Hu; Daojun Yuan; Mark A. Arick; Chuan‐Yu Hsu; Zenaida V. Magbanua; Olga Pechanova; Daniel G. Peterson; Yating Dong; Joshua A. Udall; Corrinne E. Grover; Jonathan F. Wendel (Molecular Ecology, 2026)
Gossypium hirsutum is the world's most important source of cotton fibre, yet the diversity and population structure of its wild forms remain largely unexplored. The complex domestication history of G. hirsutum combined with reciprocal introgression with a second domesticated species, G. barbadense , has generated a wealth of morphological forms and feral derivatives of both species and their interspecies recombinants, which collectively are scattered across a large geographic range in arid regions of the Caribbean basin. Here we assessed genetic diversity within and among populations from two Caribbean islands, Puerto Rico ( n = 43, five sites) and Guadeloupe ( n = 25, one site), which contain putative wild or introgressed forms. Using whole‐genome resequencing data and a phylogenomic framework derived from a broader genomic survey, we parsed individuals into feral derivatives and truly wild forms. Feral cottons display uneven levels of genetic and morphological resemblance to domesticated cottons, with diverse patterns of genetic variation and heterozygosity. These patterns are inferred to reflect a complex history of interspecific and intraspecific gene flow that is spatially highly variable in its effects. Wild cottons in both Caribbean islands appear to be relatively inbred, especially the Guadeloupe samples. Our results highlight the dynamics of population demographics in relictual wild cottons that experienced profound genetic bottlenecks associated with repeated habitat destruction superimposed on a natural ecogeographical distribution comprising widely scattered populations. These results have implications for conservation and utilisation of wild diversity in G. hirsutum .

Divergent biofilm colonization on plastics in wastewater: Accelerated maturation on polyamide versus growth inhibition on biodegradable polymers - Xiangyi Jin; Mengyao Xing; Meiying Huang; Yu Zhang; Xin Jin; Yezi Fang; Haodong Xu; Jiayi Liang; Yueyue Yu; Xiuya Xu; Shuai Liu; Yating Luo; et al. (Journal of Hazardous Materials, 2025)

Assessing land use sustainability and decoupling in Chinese cities using the improved three-dimensional ecological footprint model - Yating Dai; Le Yu; Xiangzheng Deng (Journal of Cleaner Production, 2025)

Numerical analysis of multi-source and multi-component response characteristics in the semi-airborne transient electromagnetic method - Chuantao Yu; Yating Guo; Junjie Xue; Ziqian Zhang (Journal of Applied Geophysics, 2025)

The effect of short-term storage on Antarctic krill (Euphausia superba) quality: Insights into microbial characteristics, volatile flavor compounds, trimethylamine oxide and its derivatives - Xixi Wang; Xinyu Ma; Dong Su; Yating Zhang; Junkui Miao; Xiaofang Liu; Yuan Yu; Kailiang Leng (Food Research International, 2025)

Effects of low-density polyethylene microplastics on soil functions and microbial communities across soil depths - Jing Lu; Yongfen Long; Bin Hou; Xuetao Guo; Yu Zhang; Hongjuan Bai; Yating Jia (European Journal of Soil Biology, 2025)

Perfluoroalkyl substance pollutants disrupt microglia function and trigger transcriptional and epigenomic changes - Yating Cheng; Jian-Rong Li; Hangjin Yu; Shuang Li; Boranai Tychhon; Chao Cheng; Yi-Lan Weng (Toxicology, 2025)

Engineered bimetallic nanozyme-aptamer sensor for synergistic magnetic enrichment and colorimetric detection of exosomes - Yating Song; Xiaodong Lu; Peifang Chen; Gengli Huang; Yu Li; Zhouping Wang; Junsong Yang (Chemical Engineering Journal, 2025)

A Comparative Study of Mesenchymal Stem Cells from Various Sources in Endometrial Repair: the Significant Advantages of Decidual Mesenchymal Stem Cells - Xiaochuan Yu; Lijuan Shi; Yating Zhang; Huanan Wang; Huali Wang (Stem Cell Reviews and Reports, 2025)

Diversification of Alpine Soil Animals Corroborates Uplifts and Environmental Changes of Qinghai‐Tibetan Plateau and Himalayas: Insights From Molecular Phylogeny and Cryptic Diversity of the Isotoma quadridentata Complex (Collembola: Isotomidae) - Yating Zhang; Daoyuan Yu; Huanhuan Zhang; Chen Li; Yuting Jiang; Feng Zhang; Feng Hu; Manqiang Liu (Zoologica Scripta, 2025)
The Qinghai‐Tibetan Plateau and Himalayas (QTPH) are biodiversity hotspots crucial for understanding alpine speciation. While studies have focused on flora and aboveground fauna, the impact of QTPH uplift on soil fauna diversification remains understudied. To address this research gap, we investigated a representative taxon of alpine soil animals, the Isotoma quadridentata species complex (Collembola, Isotomidae) widespread at 2300–5100 m above sea level across the QTPH. On a molecular aspect, we sequenced 2 mitochondrial (COI, 16S) and 3 nuclear (18S, 28S D1–2, 28S D7–10) markers from 79 individuals representing different populations of this complex and related species. Based on these data, our single‐locus (ABGD, ASAP) and multi‐locus (single‐rate and multi‐rate mPTP) species delimitation analyses supported 11–15 candidate species among this complex. On a morphological aspect, colour patterns varied both between and within the candidate species, suggesting caution in their use for Isotoma diagnosis. Macrochaetotaxy was largely consistent, except in AG4, which showed a distinct pattern on the head. Macroevolutionary analyses indicated a Himalayan origin for QTPH Isotoma 5.88–10.25 million years ago (Mya), with the I. quadridentata complex originating in the adjacent Emei Mountain later. This complex diversified initially in the Emei Mountain before dispersing to the northeast QTPH and back to Himalayas 3.82–6.48 Mya, followed by further speciation. These findings link the origin and diversification of QTPH Isotoma and the I. quadridentata complex to the uplift of the QTPH and subsequent environmental changes since Miocene, supporting a potential impact of this geological event on the diversification of alpine soil fauna.

Association of air pollution exposure and habitual physical activity with risk of overall and cause-specific hospital-treated infections: a UK Biobank cohort study - Zixuan Jiang; Yahang Liu; Yifang Huang; Chen Huang; Yating Yang; Ruilang Lin; Jing Wang; Runzhi Bai; Xueying Zheng; Yongfu Yu; Guoyou Qin (Environmental Research, 2025)

Engineered clay-alginate composites for tetracycline removal: Mechanistic insights and sustainable processing - Hualing Zhao; M.M.M. Ahmed; Yating Yang; Yuhan Li; Yaqi Wen; Zhaohui Li; Po-Hsiang Chang; Yu-Min Tzou (Environmental Research, 2025)

Cassie-model surface structure at nanoscale for unique air-layer mediated nanomaterial-protection - Guangyou Jia; Hongyue Yu; Xirui Huang; Yating Zhan; Qianqian Lu; Mengmeng Hou; Jia Jia; Minchao Liu; Yufang Kou; Wenxing Wang; Tiancong Zhao; Xiaomin Li; et al. (Chemical Engineering Journal, 2025)

A review of low-cost production of polyhydroxyalkanoates: Strategies, challenges, and perspectives - Jian Yao; Xin-Yu Xiao; Meng Wang; Quan Zhang; Yating Chen; Min Gou; Zi-Yuan Xia; Yue-Qin Tang (Bioresource Technology, 2025)

The stress response strategies of two typical coral Symbiodiniaceae (Cladocopium goreaui and Durusdinium trenchii) under abnormal temperatures - Jiayuan Liang; Liangyun Qin; Li Zhang; Yongqian Xu; Tianyi Niu; Zhicong Li; Yating Yang; Zhuqing Liang; Kefu Yu; Sanqiang Gong (Algal Research, 2025)

The phytochemical characteristics of Swertia mussotii Franch. and the potential for treating neuroinflammation in vitro through the NF-κB pathway - Yating Zheng; Jiajing Yu; Yanan Li; Hong Zhou; Guobiao Dai; Lijiao Yang; Rui Tan; Hezhong Jiang (Natural Product Research, 2025)

Copper isotope signatures during red earth weathering and their significance for soil reticulation (Xuancheng, South China) - Daqian Zhang; Lian Zhou; Thomas J. Algeo; Ke Yin; Lanping Feng; Yu Jiao; Yating Hu; Jinhua Liu; Hanlie Hong (Geoderma Regional, 2025)

On-site tracking of trace Aflatoxin B1 in food waste composting via a portable colorimetric sensing platform with nanozymes - Yating Lu; Fuqing He; Xu Zhu; Jing Tang; Yue Lu; Jiajia Wang; Jiangfang Yu; Li Chen; Xingyang Cheng; Tianhao Liu; Lin Tang (Journal of Hazardous Materials, 2025)

Metabolic network remodeling through PxJHE modulates temperature adaptation in a cosmopolitan insect - Gaoke Lei; Huiling Zhou; Guangyu Yu; Xin Miao; Yu Zhang; Zongyao Ma; Yating Duan; Yanting Chen; Fengluan Yao; Liette Vasseur; Shijun You (Insect Biochemistry and Molecular Biology, 2025)

Identification and validation of oxidative stress-related diagnostic markers for recurrent pregnancy loss: insights from machine learning and molecular analysis - Hui Hu; Li Yu; Yating Cheng; Yao Xiong; Daoxi Qi; Boyu Li; Xiaokang Zhang; Fang Zheng (Molecular Diversity, 2025)

Comparative evaluation of maize chromosome pretreatment using cold water and 8-hydroxyquinoline - Lulu Hou; Yating Su; Shixin Li; Haidong Yu; Yuhui Sun (Planta, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

GhCTEF2 encodes a PLS-type PPR protein required for chloroplast development and plastid RNA editing in cotton - Huan He; Mengxue Cheng; Bowen Bao; Yanan Tian; Yating Zheng; Yuzhu Huo; Zengqiang Zhao; Zongming Xie; Jianing Yu; Peng He (Plant Science, 2025)

Multi-omics analysis reveals the role of L-Glutamate in regulating cold tolerance of postharvest prune fruit - Yuanyuan Hou; Wanyu Yan; Rui Deng; Jiayi Wang; Yu Wang; Liang Wang; Jun Xing; Peng Jin; Yating Zhao (Postharvest Biology and Technology, 2025)

Ratiometric fluorescence analysis of tetracycline by dual-ligand europium-based metal-organic framework - Yating Zhong; Keying Zhang; Xinru Wang; Haibo Liang; Ying Yu; Manli Guo; Yujuan Cao; Bixia Lin (Food Chemistry, 2025)

Dipole moment modulation of perylene diimide to promote degradation and antibacterial properties - Huixia Zhu; Yu Tian; Yini Zhang; Yating Lu; Xia Yang (Chemical Engineering Journal, 2025)

Nanocomposite hydrogel with multiple metal ions coupling for effective treatment of bacteria infected wound via cascade catalysis and tissue regeneration - Yating Liu; Wenyun Mu; Yu Wang; Tao Liu; Zhenzhen Peng; Xin Chen (Chemical Engineering Journal, 2025)

Recent developments in the fabrication of food microparticles and nanoparticles using microfluidic systems - Xiao Xu; Qi Tang; Yating Gao; Shaoqin Chen; Yingying Yu; Hongliang Qian; David Julian McClements; Chongjiang Cao; Biao Yuan (Critical Reviews in Food Science and Nutrition, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Polystyrene microplastics exhibit toxic effects on the widespread coral symbiotic Cladocopium goreaui - Jiayuan Liang; Tianyi Niu; Li Zhang; Yating Yang; Zhicong Li; Zhuqing Liang; Kefu Yu; Sanqiang Gong (Environmental Research, 2025)

pH-responsive fiber membrane with high flux and photocatalytic performance for oily wastewater - Jie Wang; Bingyan Yu; Keru Hou; Yating Ji; Xiaoyan Li; Chengcheng Li; Chengjian Yao; Zaisheng Cai (Journal of Environmental Chemical Engineering, 2025)

Transparent mechanism of salted egg (white) hierarchically and synergistically driven by NaCl, NaOH and thermal treatment: Based on empirical data and molecular simulation - Le Chen; Shiqin Dong; Peng Xu; Zhuosi Yu; Yating He; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

Altered mammary gland development and pro-tumorigenic changes in young female mice following prenatal BPAF exposure - Xiaotong Ji; Jiande Li; Weiwei Wang; Peilin Li; Haoyang Wu; Linzhuo Shen; Lihong Su; Peiyun Jiang; Yating Li; Xiaoyun Wu; Yuchai Tian; Yu Liu; et al. (Environmental Research, 2025)

Construction of Zinc-based metal-organic frameworks for visual ratiometric fluorescence detection of tetracycline - Yating Zhong; Haocheng Gao; Jingqi Yang; Xinru Wang; Ying Yu; Yujuan Cao; Manli Guo; Bixia Lin (Analytica Chimica Acta, 2025)

Characteristics of Phages and Their Interactions With Hosts in Anaerobic Reactors - Yan Zeng; Xiaozhong Zhong; Yating Chen; Min Gou; Ke Yu; Yue‐Qin Tang (Environmental Microbiology, 2025)
Anaerobic digestion (AD) of organic wastes relies on the interaction and cooperation of various microorganisms. Phages are crucial components of the microbial community in AD systems, but their diversity and interactions with the prokaryotic populations are still inadequately comprehended. In this study, 2121 viral operational taxonomic units (vOTUs) were recovered from 12 anaerobic fatty acid–fed reactors. Notably, 63.1% of these vOTUs could not be assigned to any known family, revealing a substantial presence of uncharted phages specifically associated with AD environments. Over half of the vOTUs associated with hosts had the capability to infect multiple hosts, ranging from 2 to 49, with a prevalent tendency to infect 2–5 hosts. In silico predictions of phage‐host linkages uncovered that only a small fraction of vOTUs were shared across different functional groups, including fermentative bacteria, syntrophic fatty acid–oxidising bacteria (SFOB) and methanogens. Phages linked to hosts in all three groups primarily consisted of generalists and temperate species, especially those linked to SFOB. Additionally, metabolic reconstruction identified auxiliary metabolic genes participating in fatty acid degradation, methanogenesis and energy conservation. The present study provides insights into phage characteristics and their in situ interactions with prokaryotic hosts, highlighting their ecological role in AD systems.

Z-scheme H-PDI supermolecule/NH2-MIL-101(Fe) for enhanced malathion degradation: Mechanism, pathway, and toxicity assessment - Yuhang Ren; Yu Tian; Yating Lu; Dongyu Nie; Huayi Zhu; Xia Yang (Journal of Environmental Chemical Engineering, 2024)

Gelatin-crosslinked millard reaction products of sodium caseinate/ maltodextrin enhances the encapsulation efficiency and stability of krill oil microcapsules - Yating Zhang; Kailiang Leng; Xixi Wang; Zipeng Zhang; Dong Su; Ling Zhao; Xiaofang Liu; Yuan Yu; Junkui Miao; Yueqin Yu (Food and Bioproducts Processing, 2024)

Pyrolysis behavior of sewage sludge coexisted with microplastics: Kinetics, mechanism, and product characteristics - Xiaomeng Zhao; Chunli Wan; Yating Pan; Yu Fan; Xiang Liu (Journal of Environmental Management, 2024)

High-temperature stable chromium complexes bearing fluorinated PNP ligands for selective ethylene tetramerization toward 1-octene - Yating Wang; Yu Zhang; Haonan Fan; Zeyu Wang; Huijuan Shao; Ruoxing Shao; Xuzhi Zhang; Tao Jiang (Fuel, 2024)

The evaluation of Small River water pollution caused by tailing spill in the Northeast of China using high-resolution images - Yating Hu; Jingyu Liu; Yu Wang; Ge Liu; Kaishan Song; Shihong Wu; Liqiao Tian; Heng Lyu (Environmental Impact Assessment Review, 2024)

Efficient ethidium bromide removal using sodium alginate/graphene oxide composite beads: Insights into adsorption mechanisms and performance - Po-Hsiang Chang; Yating Yang; Yaqi Wen; M.M.M. Ahmed; Jou-Chieh Chang; Ting-Yu Chang; Yu-Min Tzou; Zhaohui Li; Ahmed I. Osman (Chemical Engineering Journal, 2024)

Oxaliplatin lipidated prodrug synergistically enhances the anti-colorectal cancer effect of IL12 mRNA - Hui Liu; Yating Du; Desheng Zhan; Wenjun Yu; Yan Li; Aiping Wang; Jianpeng Yin; Haiqiang Cao; Yuanlei Fu (Drug Delivery and Translational Research, 2024)

Ultrasound-assisted germination of red kidney beans: Enhancements in physicochemical and nutritional profiles - Zhihui Yu; Yating Gao; Huiling Duan; Dan Zheng; Ziqi Shang; Lixin Zhang; Yisheng Chen (Food Chemistry, 2024)

A comprehensive study of the colloidal properties, biocompatibility, and synergistic antioxidant actions of Antarctic krill phospholipids - Dong Su; Xixi Wang; Xiaofang Liu; Junkui Miao; Zipeng Zhang; Yating Zhang; Ling Zhao; Yuan Yu; Kailiang Leng; Yueqin Yu (Food Chemistry, 2024)

Design and assessment of highly stable norfloxacin/ Ca-montmorillonite (STx-1b) as oral beads - Po-Hsiang Chang; Chenxing Liang; Yating Yang; Yaqi Wen; Cheng-I Lee; Juin-Yen Ho; Chien-Yen Chen; Yu-Min Tzou (Applied Clay Science, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

A comparative study on cadmium tolerance and applicability of two Solanum lycopersicum L. cultivars - Chaoyong Ren; Nan Hou; Yuhan Zhang; Yun Wang; Yating Zhang; Yu Qiu; Shuhe Wei; Lidia Skuza; Huiping Dai (Environmental Science and Pollution Research, 2024)

Prenatal acetaminophen exposure and the developing ovary: Time, dose, and course consequences for fetal mice - Tiancheng Wu; Jing Huang; Yating Li; Yu Guo; Hui Wang; Yuanzhen Zhang (Food and Chemical Toxicology, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

The design and preparation of NDI modified MOFs for high efficiency removal of MB and Cr(VI) - Zewan Qin; Qing Guan; Yating Lu; Yu Tian; Xia Yang (Journal of Environmental Chemical Engineering, 2024)

Deep eutectic solvents promote in-situ hydrogenolysis of Evodia lepta residue in preparing small aromatic phenol ketones - Shutian Chen; Yating Jian; Yaowei Liu; Zhanying Zhang; Xinlong Li; Qiang Yu (Fuel, 2024)

A stable delivery system for curcumin: Fabrication and characterization of self-assembling acylated kidney bean protein isolate nanogels - Zhihui Yu; Yating Gao; Ziqi Shang; Tengfei Wang; Xuli He; Jian Lei; Fei Tai; Lixin Zhang; Yisheng Chen (Food Chemistry, 2024)

Structural and functional modification of miscellaneous beans protein by high-intensity ultrasound: Mechanism, processing, and new insights - Zhihui Yu; Yating Gao; Ziqi Shang; Li Ma; Yipei Xu; Lixin Zhang; Yisheng Chen (Food Hydrocolloids, 2024)

Hydrophobic sisal cellulose paper-based TENG for collecting rain energy and raindrop-based sensor - Yating Pan; Ming Li; Yuxiang Lu; Manli Lu; Bin Guo; Xianming Liu; Kaiyou Zhang; Yu Wang; Liang Feng; Aimiao Qin (Chemical Engineering Journal, 2024)

Elucidating the molecular mechanisms of pterostilbene against cervical cancer through an integrated bioinformatics and network pharmacology approach - Xiang Li; Dequan Yu; Qiming Wang; Yating Chen; Hanbing Jiang (Chemico-Biological Interactions, 2024)

Human neural stem cell secretome relieves endoplasmic reticulum stress-induced apoptosis and improves neuronal functions after traumatic brain injury in a rat model - Yating Ling; Murugan Ramalingam; Xiaorui Lv; Dongdong Niu; Yu Zeng; Yun Qiu; Yu Si; Tao Guo; Yinying Ni; Jingwen Zhang; Ziyu Wang; Hae-Won Kim; et al. (Journal of Molecular Histology, 2024)

Trim and Engine Power Joint Optimization of a Ship Based on Minimum Energy Consumption over a Whole Voyage - Yanyun Yu; Hongshuo Zhang; Zongbao Mu; Yating Li; Yutong Sun; Jia Liu (Journal of Marine Science and Engineering, 2024)
Trim optimization is an available approach for the energy saving and emission reduction of a ship. As a ship sails on the water, the draft and trim undergo constant changes due to the consumption of fuel oil and other consumables. As a result, the selection of the initial trim is important if ballasting or shifting liquid among the tanks is not considered during a voyage. According to the characteristics of ship navigation and maneuvering, a practical trim optimization method is proposed to identify the Optimal Trim over a Whole Voyage (OTWV) which makes the fuel consumption of the voyage minimum. The calculations of speed vs. draft and trim surfaces are created according to hull resistance data generated by CFD, model tests, or real ship measurements, and these surfaces are used to calculate the OTWV. Ultimately, a trim and Main Engine (ME) power joint optimization method is developed based on the OTWV to make the total fuel consumption minimum for a voyage with a fixed length and travel time. A 307000 DWT VLCC is taken as an example to validate the practicality and effect of the two proposed optimization methods. The trim optimization example indicates that the OTWV could save up to 1.2% of the total fuel consumption compared to the Optimal Trim at Initial Draft (OTID). The trim and ME power joint optimization results show that the proposed method could steadily find the optimal trim and ME power combination, and the OTWV could save up to 1.0% fuel consumption compared to the OTID in this case.

A versatile CuCo@PDA nanozyme-based aptamer-mediated lateral flow assay for highly sensitive, on-site and dual-readout detection of Aflatoxin B1 - Xu Zhu; Jing Tang; Xilian Ouyang; Yibo Liao; Haopeng Feng; Jiangfang Yu; Li Chen; Yating Lu; Yuyang Yi; Lin Tang (Journal of Hazardous Materials, 2024)

An improved DCGAN model: Data augmentation of hyperspectral image for identification pesticide residues of Hami melon - Haibo Tan; Yating Hu; Benxue Ma; Guowei Yu; Yujie Li (Food Control, 2024)

Environmental fate and risk evolution of calcium channel blockers from chlorine-based disinfection to sunlit surface waters - Qian Yin; Yuefei Ji; Yating Guo; Kyriakos Manoli; Wenzheng Chen; Lei Zhang; Xin Yu; Mingbao Feng (Water Research, 2024)

An endophytic fungus interacts with the defensin-like protein OsCAL1 to regulate cadmium allocation in rice - Tianyu Gu; Ziai Qi; Yating Wang; Siying Chen; Jing Yan; Huapeng Qiu; Yanxuan Yu; Zijun Fang; Junmin Wang; Jiming Gong (Molecular Plant, 2024)

Extraction of eutrophic and green ponds from segmentation of high-resolution imagery based on the EAF-Unet algorithm - Yating Hu; Danyang Zheng; Shuqiong Shi; Yu Wang; Ge Liu; Kaishan Song; Dehua Mao; Shihong Wu; Liqiao Tian (Environmental Pollution, 2024)

Identification a novel Ganoderma FIP gene from Ganoderma capense and its functional expression in Pichia pastoris - Jingwei Lin; Yating Liao; Sijia Yang; Taicheng Jin; Boning Yu; Kai Zhao; Yixiao Sai; Cheng Lin; Yanhua Song; Hui Ma; Zhanyong Wang (World Journal of Microbiology and Biotechnology, 2024)

Recent advance in high-intensity ultrasound modification of blue food protein: Mechanisms, functional properties and structural alterations - Zhihui Yu; Yating Gao; Xinyi Jia; Shuai Cui; Li Ma; Dan Zheng; Xin Li; Long Li; Lixin Zhang; Yisheng Chen (Trends in Food Science & Technology, 2024)

Chitosan composite films based on tea seed oil nano-microcapsules: Antibacterial, antioxidant and physicochemical properties - Qiuya Ji; Zhou Jin; Wanlu Ding; Yating Wu; Chunjie Liu; Kang Yu; Nannan Zhang; Guoguo Jin; Peiran Lu; Di Bao; Lin Mei (Food Packaging and Shelf Life, 2023)

Induced Resistance Mechanism of Bacillus velezensis S3-1 Against Pepper Wilt - Yongjie Fan; Xingjie He; Jiawei Dai; Ning Yang; Qiuyan Jiang; Zhaofeng Xu; Xiaorong Tang; Yating Yu; Ming Xiao (Current Microbiology, 2023)

A Cross-Medium Uplink Communication Model Merging Acoustic and Millimeter Waves - Yu Gai; Qi Tan; Yating Zhang; Zhengyi Zhao; Yiguang Yang; Yanyan Liu; Ruitao Zhang; Jianquan Yao (Journal of Marine Science and Engineering, 2023)
Uplink communication across the water–air interface holds great potential for offshore oil surveys and military applications. Among the various methods available for implementing uplink communication, translational acoustic-RF (TARF) communication stands out due to its ability to withstand wave interference and exhibit low absorption losses. However, the physical processes underlying such systems are currently under-researched, and channel models for evaluating its communication performance indicators are lacking. Herein, we propose a signal-to-noise ratio (SNR) channel model for evaluating the performance metrics of an uplink communication system combining acoustic and millimeter waves for the first time and validate the accuracy of the proposed model through experiments. Specifically, in the process of model construction, the physical process of the communication system was deeply studied, and the corrections of multipath effects, box vibrations, and second-order nonlinear coefficients of the amplitude of the water surface were realized. The water-to-air cross-medium communication system was built, and communication experiments were conducted to validate the feasibility of combining acoustic and millimeter wave communication. This research provides a theoretical and experimental foundation for the design and evaluation of TARF communication systems, providing valuable guidance for enhancing the system’s performance metrics and promising an innovative approach for modern seaborne communication.

Sodium butyrate alleviates deoxynivalenol-induced porcine intestinal barrier disruption by promoting mitochondrial homeostasis via PCK2 signaling - Dongfang Xue; Yating Cheng; Tiantian Pang; Yunyi Kuai; Yu An; Kuntan Wu; Yuqing Li; Mengyu Lai; Bihan Wang; Shuai Wang (Journal of Hazardous Materials, 2023)

Study on the formation pathways of characteristic volatiles in preserved egg yolk caused by lipid species during pickling - Zhuosi Yu; Lin Ye; Yating He; Xinhong Lu; Le Chen; Shiqin Dong; Xiaole Xiang (Food Chemistry, 2023)

Zirconium and neodymium isotopes record intensive felsic volcanism in South China region during the Permian-Triassic boundary crisis - Yu Jiao; Lian Zhou; Thomas J. Algeo; Lanping Feng; Jun Shen; Yating Hu; Jinhua Liu; Yan Han; Xin Hou (Chemical Geology, 2023)

Investigating the Ice-Induced Fatigue Damage of Offshore Structures by Field Observations - Yating Huang; Songsong Yu; Tai An; Guojun Wang; Dayong Zhang (Journal of Marine Science and Engineering, 2023)
The oil and natural gas resources of the Bohai Sea are mainly marginal oil fields, and there are currently a large number of structures that are approaching or have reached the end of their service life called aging structures. The interactions between ice and offshore structures could lead to significant ice-induced vibration. Ice-induced vibrations may evoke fatigue damage in tubular joints, which results in severe dangers for offshore platforms in the Bohai Sea. Dynamic ice force models and sea ice fatigue environmental parameters have not been well developed in the current design codes. It is not accurate to evaluate the fatigue damage of structures only with numerical simulation. In this paper, a faster method for evaluating fatigue damage on aging structures is proposed. Firstly, the approximate linear relationship between the fatigue hot spot stress and the vibration response of the deck structure has been discovered using dynamic analysis for jacket platform of Bohai Sea. Then, the procedure of the fatigue damage evaluation of the aging structures in the Bohai Sea is established. Finally, the numerical simulation of the structure is carried out considering ice thickness, ice velocity, ice direction, and action height of sea ice. Fatigue damage is calculated by the fatigue hot spot stress and the Palmgren–Miner rule. The measured data on the platform in the Bohai Sea are selected to obtain the fatigue hot spot stress using a mathematical model. The fatigue damage results considering the actual ice conditions of a jacket structure in the Bohai Sea are compared using the proposed method and finite element analysis. The comparison of the results verifies the rationality of the method proposed in this work.

Deep eutectic solvent assists H-β in aldol condensation of acetovanillone and p-hydroxybenzaldehyde to prepare a high density aviation oil precursor - Yating Jian; Xinlong Li; Yaowei Liu; Xiaoyan Chen; Yu Zhang; Saeid Baroutian; Qiang Yu (Fuel, 2023)

Field experiment and numerical simulation for airflow evaluation in a data center with row-based cooling - Yating Wang; Xuelian Bai; Yusen Fu; Yu Tang; Chaoqiang Jin; Zuoyang Li (Energy and Buildings, 2023)

Soil acidification induced variation of nitrifiers and denitrifiers modulates N2O emissions in paddy fields - Chaobiao Meng; Yating Xing; Yu Ding; Qichun Zhang; Hongjie Di; Caixian Tang; Jianming Xu; Yong Li (Science of The Total Environment, 2023)

Spatio-temporal variation of soil microplastics as emerging pollutant after long-term application of plastic mulching and organic compost in apple orchards - Yuanji Wang; Li Liu; Shan Cao; Jing Yu; Xiangyu Li; Yating Su; Gaochao Li; Hua Gao; Zhengyang Zhao (Environmental Pollution, 2023)

A Novel Near-Infrared Ratiometric Fluorescence Probe for Hg2+ Based on Quinoline-Fused Rhodamine Dye - Weiping Lai; Yanfei Lin; Tianqing Ye; Yating Yu; Hongwei Zhou; Lei Li; Guoliang Mao; Jianbo Wang (Journal of Fluorescence, 2023)

Recent advances in nanomedicine development for traumatic brain injury - Yating Ling; Murugan Ramalingam; Xiaorui Lv; Yu Zeng; Yun Qiu; Yu Si; Jose Luis Pedraz; Hae-Won Kim; Jiabo Hu (Tissue and Cell, 2023)

A Genome-Wide Association Study for Susceptibility to Axial Length in Highly Myopic Eyes - Qiang Lu; Yu Du; Ye Zhang; Yuxi Chen; Hao Li; Wenwen He; Yating Tang; Zhennan Zhao; Yinglei Zhang; Jihong Wu; Xiangjia Zhu; Yi Lu (Phenomics, 2023)

Riemerella anatipestifer Endonuclease I displays enzymatic activity and is associated with bacterial virulence - Ruyu Shen; Yang Yu; Zongchao Chen; Min Zhu; Yating Feng; Pengfei Niu; Shengqing Yu (Veterinary Microbiology, 2023)

To close or open the tank input water valve: Secondary water-supply systems with double tanks will induce a higher microbial risk - Dong Hu; Wenfang Lin; Jie Zeng; Heng Zhang; Yating Wei; Xin Yu (Science of The Total Environment, 2023)

Seasonal effects on aboveground biomass estimation in mountainous deciduous forests using ZY-3 stereoscopic imagery - Wenjian Ni; Tianyu Yu; Yong Pang; Zhiyu Zhang; Yating He; Zengyuan Li; Guoqing Sun (Remote Sensing of Environment, 2023)

Study on pollution evolution law of coal and rock mixed dust in coal–oil shale fully mechanized mining face: a study case - Gang Zhou; Yu Ma; Ruixin Song; Yating Hu; Yongwei Liu; Bingyou Jiang; Biao Sun (Environmental Science and Pollution Research, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Dynamic variation of fucoxanthin in Saccharina japonica during harvesting and storage processes - Yuan Yu; Junkui Miao; Xiaofang Liu; Yating Zhang; Kailiang Leng (Journal of Applied Phycology, 2023)

Efficient removal of uranium(VI) from aqueous solution by a novel phosphate-modified biochar supporting zero-valent iron composite - Ziwei Tang; Zhongran Dai; Mi Gong; Hong Chen; Xiayu Zhou; Yating Wang; Cong Jiang; Wanying Yu; Le Li (Environmental Science and Pollution Research, 2023)

Cobalt induces neurodegenerative damages through impairing autophagic flux by activating hypoxia-inducible factor-1α triggered ROS overproduction - Jianping Tang; Yanjun Li; Xu Liu; Guangxia Yu; Fuli Zheng; Zhenkun Guo; Yating Zhang; Wenya Shao; Siying Wu; Huangyuan Li (Science of The Total Environment, 2023)

MYOCD is Required for Cardiomyocyte-like Cells Induction from Human Urine Cells and Fibroblasts Through Remodeling Chromatin - Xiangyu Zhang; Lijun Chen; Xingnan Huang; Huan Chen; Baomei Cai; Yue Qin; Yating Chen; Sihua Ou; Xiaoxi Li; Zichao Wu; Ziyu Feng; Mengying Zeng; et al. (Stem Cell Reviews and Reports, 2022)

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

The effects of filter characteristics of single-filter cartridge on dust removal performance with simulation and experimental analysis - Gang Zhou; Rulin Liu; Shuailong Li; Yu Ma; Yongwei Liu; Yating Hu (Environmental Science and Pollution Research, 2022)

Preparing porous Cu/Pd electrode on nickel foam using hydrogen bubbles dynamic template for high-efficiency and high-stability removal of nitrate from water - Jialu Shi; Ya Gao; Daoru Liu; Zhanhui Shen; Jing Fan; Yating Yu; Meihui Bao; Panpan Li; Rui Yao (Environmental Science and Pollution Research, 2022)

Do proinflammatory cytokines play a role in clozapine-associated glycometabolism disorders? - Tongtong Zhao; Kai Zhang; Yelei Zhang; Yating Yang; Xiaoshuai Ning; Yu Hu; Xiaoyue Li; Yulong Zhang; Lei Xia; Zhenhua Ren; Huanzhong Liu (Psychopharmacology, 2021)
Rationale and objective Clozapine (CLZ) is the most effective drug for treatment-resistant schizophrenia but is associated with many side effects, including glycometabolism disorders. Immunological mechanisms may be involved in the development of clozapine side effects. Research relating the immunomodulatory effects of clozapine and its early markers to clinically relevant adverse events is needed to reduce the harmful side effects of clozapine. This study aimed to investigate the role of proinflammatory cytokines in clozapine-associated glycometabolism disorders. Methods We measured the effect of a range of doses of clozapine on glycometabolism-related parameters and proinflammatory cytokines levels in mice peripheral blood. We also examined the differences between these indicators in the peripheral blood of clozapine-treated schizophrenia patients and healthy controls. Furthermore, we detected proinflammatory cytokines expression in mice pancreatic tissue. Results Following clozapine administration, glucagon significantly decreased in mouse serum, and proinflammatory cytokine IL-β levels markedly increased. Clozapine reliably increased proinflammatory cytokines (IL-1β, IL-6, and TNF-α) expression in murine pancreatic tissue. Compared with healthy controls, clozapine-treated patients’ BMI, blood glucose, and proinflammatory cytokines (IL-1β, IL-6, and TNF-α) increased significantly. In clozapine-treated patients, a higher clozapine daily dosage was associated with higher levels of the proinflammatory cytokines IL-1β and IL-6, and a significant positive correlation was observed between blood glucose levels and the proinflammatory cytokines IL-6 and TNF-α. Conclusion Findings from animal experiments and clinical trials have shown clear evidence that clozapine has a regulatory effect on immune-related proinflammatory cytokines and influences glycometabolism indicators.

Inhibitory mechanism of angiotensin-converting enzyme inhibitory peptides from black tea - Yating Lu; Yu Wang; Danyi Huang; Zhuang Bian; Peng Lu; Dongmei Fan; Xiaochang Wang (Journal of Zhejiang University-SCIENCE B, 2021)

Comprehensive characterization and gene expression patterns of LBD gene family in Gossypium - Jingwen Yu; Qianwen Xie; Cheng Li; Yating Dong; Shuijin Zhu; Jinhong Chen (Planta, 2020)
Main conclusion A comprehensive account of the LBD gene family of Gossypium was provided in this work. Expression analysis and functional characterization revealed that LBD genes might play different roles in G. hirsutum and G. barbadense . Abstract The Lateral Organ Boundaries Domain (LBD) proteins comprise a plant-specific transcription factor family, which plays crucial roles in physiological processes of plant growth, development, and stress tolerance. In the present work, a systematical analysis of LBD gene family from two allotetraploid cotton species, G. hirsutum and G. barbadense , together with their genomic donor species, G. arboreum and G. raimondii , was conducted. There were 131, 128, 62, and 68 LBDs identified in G. hirsutum , G. barbadense , G. arboreum and G. raimondii , respectively. The LBD proteins could be classified into two main classes, class I and class II, based on the structure of their lateral organ boundaries domain and traits of phylogenetic tree, and class I was further divided into five subgroups. The gene structure and motif composition analyses conducted in both G. hirsutum and G. barbadense revealed that LBD genes kept relatively conserved within the subfamilies. Synteny analysis suggested that segmental duplication acted as an important mechanism in expansion of the cotton LBD gene family. Cis-element analysis predicated the possible functions of LBD genes. Public RNA-seq data were investigated to analyze the expression patterns of cotton LBD genes in various tissues as well as gene expression under abiotic stress treatments. Furthermore, RT-qPCR results found that GhLBDs had various expression regulation under MeJA treatments. Expression analysis indicated the differential functions of cotton LBD genes in response to abiotic stress and hormones.

Quantitative climatic reconstruction of the Last Glacial Maximum in China - Haibin Wu; Qin Li; Yanyan Yu; Aizhi Sun; Yating Lin; Wenqi Jiang; Yunli Luo (Science China Earth Sciences, 2019)

Evolution of the relative abundance of C 4 plants on the Chinese Loess Plateau since the Last Glacial Maximum and its implications - Wenqi Jiang; Jianyu Wu; Haibin Wu; Qin Li; Yating Lin; Yanyan Yu (Journal of Quaternary Science, 2019)
Understanding the distribution of C 3 and C 4 plants and its forcing mechanisms since the Last Glacial Maximum (LGM) is important for anticipating their possible response to future climate change. The spatiotemporal pattern of C 4 plant abundance on the Chinese Loess Plateau (CLP) is complex and the dominant causal factors are contentious. Here, we use δ 13 C records of organic matter in paleosols from the CLP to reconstruct changes in the representation of C 4 plants since the LGM. The results indicate that the relative abundance of C 4 plants increased after the LGM, reaching a maximum during 10–6 ka bp, and then decreased. Spatially, the representation of C 4 plants was characterized by increasing values from north‐west to south‐east. In addition, the smallest spatial difference (∼10%) in the representation of C 4 plants between the north‐west and south‐east parts of the CLP was during the LGM, and the largest difference (∼30%) was during the early Holocene. We combined our findings with output from the BIOME4 model to study the sensitivity of C 4 plants to changes in climate and atmospheric CO 2 concentration. The results suggest that increasing temperature was the dominant factor driving C 4 plant expansion on the CLP since the LGM.

Immunization with Chlamydia psittaci plasmid-encoded protein CPSIT_p7 induces partial protective immunity against chlamydia lung infection in mice - Yuan Tan; Yumeng Li; Yang Zhang; Jian Yu; Yating Wen; Chuan Wang; Man Xu; Qian Chen; Chunxue Lu; Yimou Wu (Immunologic Research, 2018)

Network analysis of eight industrial symbiosis systems - Yan Zhang; Hongmei Zheng; Han Shi; Xiangyi Yu; Gengyuan Liu; Meirong Su; Yating Li; Yingying Chai (Frontiers of Earth Science, 2016)

Regional environmental risk assessment for the Nanjing Chemical Industry Park: an analysis based on information-diffusion theory - Xiaojie Meng; Yan Zhang; Xiangyi Yu; Junhong Bai; Yingying Chai; Yating Li (Stochastic Environmental Research and Risk Assessment, 2014)